Assessing North Atlantic right whale health : threats, and development of tools critical for conservation of the species - Moore, Michael J.; Rowles, Teresa K.; Fauquier, Deborah A.; Baker, Jason D.; Biedron, Ingrid; Durban, John W.; Hamilton, Philip K.; Henry, Allison G.; Knowlton, Amy R.; McLellan, William A.; Miller, Carolyn A.; Pace, Richard M.; et al. (Diseases of Aquatic Organisms, 2021)
NA14OAR4320158 funded the drafting of this manuscript. Whaling has decimated North Atlantic right whales Eubalaena glacialis (NARW) since the 11th century and southern right whales E. australis (SRW) since the 19th century. Today, NARWs are Critically Endangered and decreasing, whereas SRWs are recovering. We review NARW health assessment literature, NARW Consortium databases, and efforts and limitations to monitor individual and species health, survival, and fecundity. Photographs are used to track individual movement and external signs of health such as evidence of vessel and entanglement trauma. Post-mortem examinations establish cause of death and determine organ pathology. Photogrammetry is used to assess growth rates and body condition. Samples of blow, skin, blubber, baleen and feces quantify hormones that provide information on stress, reproduction, and nutrition, identify microbiome changes, and assess evidence of infection. We also discuss models of the population consequences of multiple stressors, including the connection between human activities (e.g. entanglement) and health. Lethal and sublethal vessel and entanglement trauma have been identified as major threats to the species. There is a clear and immediate need for expanding trauma reduction measures. Beyond these major concerns, further study is needed to evaluate the impact of other stressors, such as pathogens, microbiome changes, and algal and industrial toxins, on NARW reproductive success and health. Current and new health assessment tools should be developed and used to monitor the effectiveness of management measures and will help determine whether they are sufficient for a substantive species recovery. Peer reviewed